Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1982
DOI: 10.1079/bjn19820098
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diet and microbial activity in the digestive tract on digestibility, and nitrogen and energy metabolism in rats and pigs

Abstract: 1. Balance trials with respiration measurements were performed with twelve rats and twelve pigs given either low-or high-crude-fibre diets. There were six collection periods with the rats over a live-weight range of 86264 g and three collection periods with the pigs over a live-weight range of 30-55 kg. Measurements were made on the influence of microbial activity in the digestive tract on digestibility and nitrogen and energy metabolism. Dietary inclusion of the antibiotic Nebacitin was the method used to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 19 publications
(4 reference statements)
0
26
0
1
Order By: Relevance
“…1984 Dietary antibiotics have been shown to increase the apparent absorption of N from the small intestine (Just et al 1981;Eggum et al 1982), and although the present data suggest that SM may alter fermentation in the gastrointestinal tract of the pig, the site of this action is not known. The …”
mentioning
confidence: 56%
“…1984 Dietary antibiotics have been shown to increase the apparent absorption of N from the small intestine (Just et al 1981;Eggum et al 1982), and although the present data suggest that SM may alter fermentation in the gastrointestinal tract of the pig, the site of this action is not known. The …”
mentioning
confidence: 56%
“…Along with this, calcium level was found as 7.34 mg/dl and 8.01 mg/dl in male and female cattle respectively (p= 0.21) was agreed with the Kaneko, (1989). A parameter of kidney function test namely creatinine was estimated and no significance is found in between male (5.68 mg/dl) with female (5.51 mg/dl) cattle (p= 0.48) was agreed with Eggum et al (1982). In this present study we found that different concentration of glucose (mg/dl), total protein (g/dl), albumin (g/dl), cholesterol (mg/dl), LDL ( mg/dl), SGPT (U/L), SGOT (U/L), ALP (U/L), magnesium (mg/dl), calcium (mg/dl), phosphorus (mg/dl), uric acid (mg/dl) and creatinine (mg/dl) in different groups of cattle.…”
Section: Discussionmentioning
confidence: 99%
“…The results was also indicated that the uric acid was increasing at the increased of age but the variation was not significant ((p>0.05). Uric acid is a primary metabolic product of protein metabolism (Eggum et al, 1982). No significant variation (p > 0.05) was observed in creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to human nutrition, however, the use of rats as models in pig nutrition is less well accepted, because it is relatively easy to obtain results from the pig itself. The great value of the rat as a model lies in the economic factors associated with facilities and time, which allows the use of large numbers of animals and a rapid production of results.The digestibility of energy and protein in the pig and rat is highly correlated for several diets (Eggum, 1973;Eggum et al 1982), indicating that the rat may be a good model for pigs for these variables. However, it is less clear whether rats are also suitable models for pigs with regard to the digestibility of other nutrients and the fermentation of non-digestible carbohydrates, primarily as NSP, by the gut microflora.…”
mentioning
confidence: 99%